A governess's guide to passion and peril - Collins, Manda (Collins, Manda. Ladies most scandalous, 2024)
"Jane Halliwell once dreamed of exploring the world as an acclaimed journalist - but those dreams (and her dowry) died with her father. Now, she works as a governess, safe on England's shores. But when her current employer is murdered, adventure seems to finally be knocking (rather brutely) at her door. Only the danger is more lethal than she expected . . . for standing outside is the same lord who once broke her tender heart. Lord Adrien Fielding considered Jane a dear companion - but no more, as his heart was already bound to the Foreign Office. However, after years of serving abroad as a spy, he's now looking to retire . . . and perhaps settle down with a family of his own. But when his mentor is killed under mysterious circumstances, he has no choice but to join the investigation as his final job. To Adrien's reluctant admiration, Jane is no longer the demure girl he remembers and refuses to let him question her charges. He'll need all his skills in diplomacy and espionage to convince Jane he means them no harm. Only Adrien soon finds himself the one seduced, as he realizes he feels more than friendship toward Jane. But with a killer haunting their steps and years of secrets between them, is it too late for their chance at love?"--